Ovariohysterectomy pada kucing liar - Prayoga, Shabrina Fauzia; Megawati, Neneng Ismi; Arifin, Eko Muhammad Zaenal; Nangoi, Lianny (Universitas Airlangga, 2021)
Free-roaming feral cats are a threat to society as they are the source of some zoonotic diseases. Reproductive sterilization of feral cats, especially the female ones (spay), will reduce the population of feral cats, which in turn will also improve the welfare of the cats themselves.A female stray cat was brought to the clinic for sterilization. The results of the physical examination showed that the cat was in good health. The sterilization method used was ovariohysterectomy through the caudal midline approach. Postoperative therapy given was injection of Sulfadiazine and Trimethoprim (30 mg/kg BW) and Dexamethasone (0.5 mg/time intramuscularly), Amoxicillin syrup (20 mg/kg body weight q8h), and topical povidone-iodine on the surgical wound. The wound healing process went well without complications. On day-11, the stitches were removed with the condition of the surgical wound had dried up.